Development of Adapted Guitar to Improve Motor Function after Stroke: Feasibility Study in Young Adults - Dechenaud, Marcelline; Laidig, Daniel; Seel, Thomas; Gilbert, Hunter B.; Kuznetsov, Nikita A. (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2019)
Recent research indicates that music-supported therapies may offer unique benefits for rehabilitation of motor function after stroke. We designed an adapted guitar and training task aimed to improve coordination between rhythmic and discrete movements because individuals recovering from stroke have greater difficulty performing discrete vs. rhythmic movements. In this paper, we report a feasibility study on training to play this adapted guitar in healthy young adults. Subjects (N = 10) practiced two rhythmic strumming patterns over three consecutive days using their non-dominant hand guided by an audiovisual metronome (60 bpm). They were also instructed to press a foot pedal while maintaining the strumming movement. Elbow and wrist kinematics were estimated using wireless inertial measurement units. Results showed positive mean asynchrony between strum onsets and metronome onsets, and a decrease in the standard deviation of mean asynchrony over practice. In early practice, participants slowed the strumming movement when they pressed the foot pedal, but this interference decreased on days two and three. Smoothness of the elbow movement during the strum phase, which includes the contact with the strings, increased over practice, while smoothness of the return phase did not change over practice. The predominant joint coordination pattern used for the strum phase consisted of elbow extension coupled with elbow pronation, wrist extension, and ulnar deviation. We discuss how these results fit into current music-based rehabilitation literature and outline directions for future applications of this music-supported intervention.
CRIS-Team Scopus Importer:2021-03-31